Conversion Surgery for Stage IV Gastric Cancer - Zhang, Fei; Huang, Xuanzhang; Song, Yongxi; Gao, Peng; Zhou, Cen; Guo, Zhexu; Shi, Jinxin; Wu, Zhonghua; Wang, Zhenning (Frontiers in Oncology, 2019)
Conversion surgery for gastric cancer (GC) has received increasing attention in recent years. This approach encompasses cases where surgical resection is initially identified to be inapplicable for a tumor but then, following chemotherapy, surgery with the intention of R0 resection can be performed. Although advances in conversion surgery for GC have improved survival rates, choices of chemotherapy regimens, indications for conversion surgery, optimal intervals between surgery and chemotherapy, and postoperative chemotherapy all remain controversial. The objective of this review is to summarize the current state of conversion surgery for stage IV GC.